Anonim ortaklık genel kurul kararlarının iptalinde davacı sıfatı - Bilgetekin, Emine (My University, 2019)
Anonim ortaklıkta genel kurul olağan ya da olağanüstü toplanır. Bu şekilde toplanan genel kurulda alınan kararlar tüm pay sahipleri bakımından geçerli olur. Anonim ortaklık genel kurul kararları hukuki işlem niteliğini haizdir. Bu sebeple kararların yokluğuna ilişkin TTK’da düzenleme bulunmasa dahi genel kurul kararları yokluk yaptırımına maruz kalabilir. Genel kurul kararlarının butlanı ve iptali ise TTK’ da özel olarak düzenlenmiştir. Öncelikle hangi durumlarda anonim ortaklık genel kurul kararlarının yokluğunun, butlanının söz konusu olduğu açıklanmaya çalışılmış, sonrasında ise hangi kararların iptal edilebilirlik yaptırımına tabi olacağı açıklanmıştır. Genel kurulda alınan kararların TTK m. 445’de belirtildiği üzere Kanuna, esas sözleşmeye, özellikle dürüstlük kuralına uygun olması gerekir. Aksi halde TTK m. 446’da belirtilen kişiler bu kararların iptali için dava açabilirler. TTK m. 446’da dava açabilecek kişiler olarak pay sahipleri, yönetim kurulu ve kararların yerine getirilmesi kişisel sorumluluğuna yol açacaksa her bir yönetim kurulu üyesi gösterilmiştir. Ayrıca SerPK’da SPK’ya da belirli koşullarda iptal davası açma yetkisi verilmiştir. Dolayısıyla bu belirtilen kişi ve kurumlar kanunda gerekli koşulları sağladıkları takdirde anonim ortaklık genel kurul kararları aleyhine iptal davası açabilirler. Kanun’da belirtilen bu kişiler haricinde kimlerin iptal davası açabileceği ise tartışma konusu olmuştur. Özellikle pay üzerinde intifa hakkı bulunması halinde intifa hakkı sahibinin mi yoksa pay sahibinin mi iptal davası açabileceği tartışması mevcuttur. Ya da payın devri halinde iptal davasını yeni pay sahibinin açıp açamayacağı, ya da açılan bir iptal davasına devam edip edemeyeceği tartışması bulunmaktadır. Tezde pay üzerinde rehin hakkı bulunması, hapis hakkı bulunması payın saklama ya da kullanım ödüncü sözleşmesine konu olması, payın haczedilmesi, pay sahibinin iflas etmesi vb. hallerde iptal davasının kimin tarafından açılabileceği açıklanmaya çalışılmıştır. Anonim ortaklık genel kurul kararlarının iptaline ilişkin verilmiş Yargıtay içtihatlarından da yararlanılarak, tezin, uygulama ile bağlantısı sağlanmaya çalışılmıştır.

AbstractIn joint stock companies, a general assembly convenes in ordinary or extraordinary cases. The decisions reached at such assemblies are considered valid for all shareholders. As decisions by a general assembly of any joint stock company are legal actions by their nature, they may be deemed null, void or cancelled. Although no provision on the nullity of such decisions exists in the Turkish Commercial Code, the declaration of decisions by a general assembly as void and cancelled is regulated by the Turkish Commercial Code. This study firstly attempts to explain which situations can lead to the declaration of decisions by the general assembly as null or void, and secondly, discusses the decisions which may be subject to the sanction of cancellation. Common regulations on the cancellation of decisions by a general assembly are enshrined in Article 445 of the Turkish Commercial Code and its subsequent provisions. According to Article 445 of the Turkish Commercial Code, any decision by a general assembly shall comply with laws, articles of association, in particular with good faith. Otherwise, the persons listed in Article 446 of the Turkish Commercial Code can bring an action for the cancellation of these decisions. In accordance with Article 446 of the Turkish Commercial Code, the persons entitled to bring an action are shareholders, a general assembly and if the execution of decisions may yield their personal liability, each member of a general assembly. In addition, according to the Capital Markets Law No 6362, the Capital Markets Board is also authorized to file a claim in certain circumstances. Therefore, these persons and entities may file a claim against decisions by a general assembly of joint stock companies, provided that the requirements specified by law are met accordingly. However, there is still an argument over the persons granted a right to bring an action for cancellation, except those determined by law. Especially, in cases when the share is subject to the right of usufruct, it is unclear whether the owner of the right of usufruct or the shareholder is entitled to file a claim for cancellation. Furthermore, in cases of the assignment of shares, the new owner’s right to bring a claim for cancellation or resume the case of cancellation already initiated is a matter dispute. In this study, the persons entitled to bring an action for cancellation in cases when a share is subject to pledge or custody or the storage or loan contract or seizure or the bankruptcy of a shareholder or similar conditions are also discussed. The connection between this study and practice has been secured by the contribution of the case law of the Supreme Court of the Republic of Turkey in relation to the cancellation of decisions by a general assembly of joint stock companies.
Keywords: action for annulment; Anonim ortaklık; Civil law; davacı sıfatı Joint stock company; genel kurul; genel kurul kararı; Hukuk; iptal davası; Law; Medeni hukuk; plaintif; the decisions of the general board; the general board